Aerobic and Strength Training Reduces Adiposity in Overweight Latina Adolescents - DAVIS, JAIMIE N. (2009)
PURPOSE: To date, no study has examined the synergistic effects of a nutrition and combination of aerobic and strength training (CAST) on both adiposity and metabolic parameters in overweight Latina adolescent females. The goal was to assess if a 16-wk nutrition plus CAST pilot study had stronger effects on reducing adiposity and on improving glucose/insulin indices compared with control (C), nutrition only (N), and a nutrition plus strength training (N + ST) groups. METHODS: In a 16-wk randomized trial, 41 overweight Latina girls (15.2 ± 1.1 yr) were randomly assigned to C (n = 7), N (n = 10), N + ST (n = 9), or N + CAST (n = 15). All intervention groups received modified carbohydrate nutrition classes (once a week), whereas the N + ST also received strength training (twice a week) and the N + CAST received a combination of strength and aerobic training (twice a week). The following were measured before and after intervention: strength by one repetition maximum, physical activity by the 7-d accelerometry and the 3-d physical activity recall, dietary intake by 3-d records, body composition by dual-energy x-ray absorptiometry (DEXA), glucose/insulin indices by oral glucose tolerance test, and intravenous glucose tolerance test with minimal modeling. Across intervention group, effects were tested using ANCOVA with post hoc pairwise comparisons. RESULTS: There were significant overall intervention effects for all adiposity measures (weight, body mass index [BMI], BMI z-scores, and DEXA total body fat), with a decrease of 3% in the N + CAST group compared with a 3% increase in the N + ST group (P ≤ 0.05). There was also an intervention effect for fasting glucose with the N group increasing by 3% and the N + CAST group decreasing by 4% (P ≤ 0.05). CONCLUSION: The CAST was more effective than nutrition alone or nutrition plus strength training for reducing multiple adiposity outcomes and fasting glucose in overweight Latina girls. However, further research investigating and identifying intervention approaches that improve both adiposity and insulin indices, particularly in high-risk populations, are warranted.